Epidemiology Of Voice Disorders Among Government School Teachers - An Analytical Cross-Sectional Study from Kancheepuram District - Sankar, Gowthaman; Ganesan, Vijayakrishnan; Shantharam, Raja Vel; Palanisamy, Kaveri; Katam, Indraja (National Journal of Community Medicine, 2022)
Background: Voice disorders cause undesirable effects on school teachers such as reducing their quality of life, decrease in work performance affecting the quality of education, job absenteeism, and reduced social activities as well. Methodology: Voice disorder among teachers was assessed through the “Voice handicap Index”, which was developed by Jacobson et al in 1997 to self-assess the severity of voice disorder in dysphonia patients Results: The overall prevalence of voice disorder among government school teachers was found to be 46.5% with a 95% confidence interval from 41.5% to 51.5%. Using Backward Wald, the binary logistic regression analysis showed that female teachers (AOR 1.6, p<0.01*), teaching experience less than 10 years (AOR 2.4, p<0.01*), and teaching hours more than 21 hours per week (AOR 6.7, p<0.01*) had a significant association with voice disorders. Conclusion: The prevalence of voice disorder was found to be high since teachers are professional voice users. The study also recommends that teachers must receive the required health education on the ergonomic risk factors that they will come into contact with in their daily lives as part of their jobs.